Thiocillin contributes to the ecological fitness of Bacillus cereus ATCC 14579 during interspecies interactions with Myxococcus xanthus - Müller, Susanne; DeLeon, Orlando; Atkinson, Samantha N.; Saravia, Fatima; Kellogg, Stephanie; Shank, Elizabeth A.; Kirby, John R. (Frontiers in Microbiology, 2023)
The soil-dwelling delta-proteobacterium Myxococcus xanthus is a model organism to study predation and competition. M. xanthus preys on a broad range of bacteria mediated by lytic enzymes, exopolysaccharides, Type-IV pilus-based motility, and specialized metabolites. Competition between M. xanthus and prey bacterial strains with various specialized metabolite profiles indicates a range of fitness, suggesting that specialized metabolites contribute to prey survival. To expand our understanding of how specialized metabolites affect predator-prey dynamics, we assessed interspecies interactions between M. xanthus and two strains of Bacillus cereus. While strain ATCC 14579 resisted predation, strain T was found to be highly sensitive to M. xanthus predation. The interaction between B. cereus ATCC 14579 and M. xanthus appears to be competitive, resulting in population loss for both predator and prey. Genome analysis revealed that ATCC 14579 belongs to a clade that possesses the biosynthetic gene cluster for production of thiocillins, whereas B. cereus strain T lacks those genes. Further, purified thiocillin protects B. cereus strains unable to produce this specialized metabolite, strengthening the finding that thiocillin protects against predation and contributes to the ecological fitness of B. cereus ATCC 14579. Lastly, strains that produce thiocillin appear to confer some level of protection to their own antibiotic by encoding an additional copy of the L11 ribosomal protein, a known target for thiopeptides. This work highlights the importance of specialized metabolites affecting predator-prey dynamics in soil microenvironments.